Exploring the Drivers of IPO Initial Return in Emerging Market: A Logistic Regression Analysis using Non-Financial Information - Ash. Shiddiq, Muh. Hasbi; Arief, Fitriani (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to provide a new perspective on the phenomenon of initial returns in IPO stocks by incorporating non-financial information, namely underwriter reputation, listing board, and Sharia-compliant stock status. The underwriter variable is measured using research reports from PT Stockbit Sekuritas, which makes it distinct from previous studies that used different measures for underwriter reputation. The sample consisted of 192 IPOs listed between 2022 until April 15, 2025. Data were collected through documentation from publications by the Indonesia Stock Exchange and PT Stockbit Sekuritas. The data analysis begins with assessing model fit using the Akaike Information Criterion (AIC), Bayesian Information Criterion (BIC), and Pseudo R². Binomial logistic regression is employed to analyze the data, with interpretation based on odds ratios. The findings reveal that reputable underwriters and sharia-compliant status have a positive and significant effect on IPO initial returns, while the listing board does not have a significant impact. Specifically, IPOs managed by reputable underwriters are 3.32 times more likely to generate initial returns compared to those handled by non-reputable underwriters. Similarly, sharia-compliant IPOs are 2.35 times more likely to deliver initial returns compared to non-sharia IPOs. This study provides empirical evidence that non-financial information disclosed in IPO prospectuses should also be considered to complement financial information. Accordingly, the findings offer practical implications for investors, suggesting that they should consider underwriter reputation and sharia-compliant categorization as important factors when making IPO investment decisions.